Processing of quick cooking rice using three high amylose rice varieties - Maceda, Gerald John A.; Azanza, Ma Patricia V. (1998)
The laboratory production of quick cooking rice was done using three test rice varieties namely: IR 42; 36; and 74. Hydration using a 1:1 mixture of 0.5% sodium citrate and 0.5% calcium chloride maintained at 50°C for 15 min showed moisture ratio and volume ratio values ranging from 1.37-1.48 and 1.17-1.22, respectively. Optimum gelatinization conditions using steam under pressure at 15 psi for 2 min were establish with water ratio of 1:1.0, 1:1.0 and 1:0.8 for the variety IR 42, 36 and 74, respectively. These conditions resulted to 100% gelatinization of the rice samples with minimum clumping and breakage. Convective air drying, freeze drying and combination freeze and convective drying resulted to drying times in the range of 0.75-3.0 h for to attain 10% moisture content in QCR products. Rehydration by soaking in water maintained at 60-70°C for 15 min resulted to moisture uptake, volume ratio, percent clumpiness and breakage values ranging from 2.28-5.13, 1.46-3.28, 0-5% and 6-25%, respectively. The moisture ratio, volume ratio, percent clumping and breakage values of the QCR samples rehydrated by boiling in water at 100°C for 5 min ranged from 1.90-5.99, 1.33-3.48, 0-5% and 0-25%, respectively. Variations in quality of the rehydrated samples was attributed to varying gelatinization temperature characteristics of the samples. The study recommends to evaluate the storage stability of the QCR products produced.
Thesis (BSFT)--University of the Philippines Diliman
Keywords: Rice -- Philippines